Propuesta de modelo de control interno para el área de facturación y cartera para la empresa Agencia de Aduanas Valley Groups S.A.S de la ciudad de Cali Valle a partir de la metodología COSO - Leal Ramírez, Vivian Katherine (Universidad Antonio Nariño, 2022)
The company Agencia de Aduanas Valley Groups S.A.S was born with the fundamental ob jective of providing customs brokerage services and initially offering logistics solutions to Vallecaucan companies in their need to import and export their products.